Nicotine metabolite ratio and smoking outcomes using nicotine replacement therapy and varenicline among smokers with and without psychiatric illness. (September 2018) - Clyde, Matthew; Pipe, Andrew; Els, Charl; Reid, Robert; Fu, Angel; Clark, Alexa; Tulloch, Heather
Introduction: It has been suggested that the effectiveness of nicotine replacement smoking cessation pharmacotherapy may be enhanced by assessing rates of nicotine metabolism using the nicotine metabolite ratio – which reflects differences in the activity of the CYP2A6 hepatic enzyme – and titrating doses appropriately. To date, supporting evidence is equivocal, with little information regarding the assessment and effectiveness of the nicotine metabolite ratio among smokers with psychiatric conditions. Methods: The nicotine metabolite ratio of 499 smokers from the FLEX trial was determined using urine samples obtained at baseline. They were randomized to receive either: standard transdermal nicotine (nicotine replacement therapy); extended nicotine replacement therapy + adjunct nicotine agent; or varenicline. Primary cessation outcomes were seven-day point prevalence at 5, 10, 22, and 52 weeks post-target quit date, comparing across treatment and psychiatric status. Our principal analysis employed logistic regression (outcome: abstinence), using slow metabolizers as the reference category. Results: No differences were observed by nicotine metabolite ratio classification (slow, moderate, fast) with respect to any demographic or smoking-related variables. Nicotine metabolite ratio class did not predict smoking cessation in either the overall sample, or by treatment condition at any time-point (week 52 moderate metabolizers: odds ratio 1.34, 95% confidence interval (0.68–2.63), p =0.394; fast metabolizers: odds ratio 1.04 (0.56–1.91), p =0. 906). Conclusion: Our results did not find any associations between nicotine metabolite ratio and cessation outcomes among smokers using nicotine replacement therapy or varenicline with and without lifetime psychiatric conditions.